Volatility of Technology and Healthcare Sectors Before and During Covid-19 Pandemic - Mahussin, Norlida; Mohd Jaapar, Asmah; Mustafa, Luqman Anwar (Malaysian Journal of Science Health & Technology, 2021)
The study investigates the effect of the Covid-19 on the volatility of the technology and healthcare sector stock index in Malaysia. The two sectors pose considerable attention during the pandemic due to the increase in demand for healthcare products and digital services. The volatilities are estimated using the GARCH model for the period before and after the implementation of the nationwide movement order control using daily data from September 2019 to September 2020. The finding shows that the Covid-19 pandemic caused a volatility jump for the technology sector index in March 2020 but subsided afterward with estimated conditional volatility revert to normal in the middle of April 2020. However, during the high uncertainty period, the healthcare sector shows a steady increase in volatility beginning in March 2020 till the end of September 2020. The study confirms that there is a significant difference in the volatility of healthcare and technology sectors before and during the Covid-19 outbreak. The outbreak has a significant impact on increasing the volatilities for both sectors but is impacted in different magnitude.